La agricultura de precisión dentro del manejo sostenible de suelos - Mariscal Rocafuerte, Hernán Antonio (2019)
SUMMARY The purpose of this document was to find alternatives for precision agriculture in sustainable soil management, considered as the correct application of the use of machinery, at the right time and in the exact place, and it is also a work process based on the generation, measurement and analysis of georeferenced information to achieve not only a thorough knowledge of the sources of variability within a lot, but also to control the quality with which we are performing the field tasks, verify the quality of decisions, identify bad practices, among other applications. The objectives set were to describe the effect of precision agriculture in the sustainable management of soils and detail the sustainable management of soils through precision agriculture techniques. To carry out the research instrument, information was collected from books, magazines, articles, web pages, in order to carry out the information obtained in this document. This information was submitted to the technique of analysis, summary and synthesis on precision agriculture in sustainable soil management. The detailed conclusions determined that precision agriculture influences the increase in efficiency, productivity and profit margin, being the main goal in which the entire production unit is designed, based on the integration of information and production; Precision agriculture promotes the generation of appropriate decisions for crop production using information technology to capture multiple data, helping in making appropriate decisions regarding management, techniques, economy and environment; The capture of agronomic information to meet the needs of producers is a precise production system within precision agriculture, using technological methods and tools to gather information in real time on what can happen in soils and in crops and making decisions that increase crop yields such as sustainable soil management and modern technology will ensure an increase in the quality of life of man if used properly. Keywords: precision agriculture, technology, georeference